Prolactin and growth hormone affect metaphase-II chromosomes in aging oocytes via cumulus cells using similar signaling pathways - Lebedeva, Irina Y.; Singina, Galina N.; Lopukhov, Alexander V.; Shedova, Ekaterina N.; Zinovieva, Natalia A. (Frontiers in Genetics, 2015)
General senescence of the adult organism is closely connected with reproductive one. Meanwhile, the age-related reduction in the female fertility is primarily associated with a decline in the gamete quality. Molecular and cellular changes in oocytes of old mammalian females are very similar to those occurring during aging of matured ova of their young counterparts, suggesting similarities in underlying mechanisms. The aim of the present work was to study actions of two related pituitary hormones, prolactin (PRL) and growth hormone (GH), on age-associated modifications of metaphase-II (M-II) chromosomes in bovine oocytes using a model of the prolonged culture. We analyzed: (1) effects of PRL and GH on abnormal changes in the chromosome morphology in aging matured oocytes and the role of cumulus cells in these effects and (2) signaling pathways involved in the hormone actions. During the prolonged culture of oocytes, a gradual rise in the frequency of destructive modifications of M-II chromosomes was revealed. In the case of cumulus-enclosed oocytes (CEOs), PRL and GH exerted dose-dependent biphasic effects on the frequency of these modifications. Both PRL (50 ng/ml) and GH (10 ng/ml) decelerated the abnormal chromosome changes in CEOs, but did not affect the chromosome configuration in denuded oocytes. Concurrently, the presence of PRL and GH receptors in cumulus cells surrounding matured oocytes was demonstrated. Attenuating effects of both hormones on the chromosome modifications in aging CEOs were abolished by PP2 (an inhibitor of Src-family tyrosine kinases), triciribine (an inhibitor of Akt kinase), and calphostin C (a protein kinase C inhibitor). Our findings indicate that PRL and GH can exert the similar decelerating action on age-associated alterations in the M-II chromosome morphology in bovine ova, which is mediated by cumulus cells and may be related to activation of Src-family tyrosine kinases as well as Akt- and protein kinase C-dependent signal pathways.